Step-by-step explanation:
The coordinate of the center is given below as
![\begin{gathered} A=(3,2) \\ A(h,k)=(3,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jy9mzgik7htl3ahhak5ngecu37mv5t4wbw.png)
From the image below
The general equation of a circle is represented below as
![\begin{gathered} (x-h)^2+(y-k)^2=r^2 \\ (h,k)=center \\ r=radius \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/frzya3qnbpdkuiy0j7udryyz5wts1x4nqk.png)
To figure out the value for r, we will use the formula below
![\begin{gathered} r=√((x_2-x_1)^2+(y_2-y_1)^2) \\ x_1=3,x_2=7 \\ y_1=2,y_2=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k0fetp5nyendn46ri1704v850ygavrnf3p.png)
By substituting the values, we will have
![\begin{gathered} r=√((x_2-x_1)^2+(y_2-y_1)^2) \\ r=√((7-3)^2+(2-2)^2) \\ r=√(4^2+0^2) \\ r=√(16) \\ r=4 \\ r^2=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/14rc15ixr5z7traj3pattvdyc1gdw4cvbw.png)
Hence,
The final answer by substituting the center and the radius will be given below as
![\begin{gathered} (x-h)^(2)+(y-k)^(2)=r^(2) \\ (x-3)^2+(y-2)^2=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7jkrxiei3pqqes8rll0a9yskyjk1gejms.png)
Hence,
The final answer is
![(x-3)^(2)+(y-2)^(2)=16](https://img.qammunity.org/2023/formulas/mathematics/college/wcoxreos8oz6tt44xb9v9vvjv8ahit9qaj.png)